Project-Based Learning Model with Visit Home Approach and Learning Style on Social Studies Learning Outcomes in Elementary Schools - Nurhasanah; Tanjung, Samsidar; Matondang, Zulkifli (Universitas Pendidikan Ganesha, 2024)
Implementing the PBL Model using the Visit Home approach requires more time, so it becomes a challenge, mainly if learning time is limited. This research aims to analyze the differences in social studies learning outcomes for students taught using the project-based learning model assisted by the home visit method compared to the online learning model. This type of research is experimental research. The sample in this study was class V students consisting of 2 class groups, namely V-A with 27 students and class V-B with 27 students. Data collection methods use tests and questionnaires. The data collection instruments are questionnaires and test questions. The data analysis techniques used are descriptive and inferential statistical techniques. The research results show differences in social studies learning outcomes for students taught using the project-based learning model assisted by the home visit method compared to online media. Secondly, there are differences in social studies learning outcomes between students with visual, auditory, and kinesthetic learning styles. Third, there is an interaction between learning approaches and learning styles on students' social studies learning outcomes. It was concluded that the project-based learning model assisted by the home visit method could improve student learning outcomes.